Losses Reduction and Voltage Improvement Using Optimum Capacitor Allocation by PSO in Power Distribution Networks - Hasan, Ihsan Jabbar; Gan, Chin Kim; Shamshiri, Meysam; Ismadi , Bugis; Ab Ghani, Mohd Ruddin (Praise Worthy Prize, 2013)
Capacitor installation is one of the common methods of the reactive power compensation in power distribution networks. In this paper, the optimum capacitor placement and sizing has been executed in the distribution network in terms of power losses minimization and voltage profile improvement. The maximum and minimum bus voltage and maximum possible capacitor size are the constraints of optimum capacitor placement and sizing problem which considered as a penalty factor in the objective function. In order to solve the obtained objective function, the Particle Swarm Optimization (PSO) is utilized to find the best possible capacitor placement and size. The OpenDSS engine is utilized to solve the power flow through Matlab coding interface. To validate the functionality of the proposed method, the IEEE 13 node and IEEE 123 node test systems are implemented. In both cases, the optimum capacitor allocation has been applied by the proposed PSO to find the best possible capacitor location and size. The result shows that the proposed algorithm is more cost effective and has lower power losses compare to the IEEE standard case. In addition, the voltage profile has been improved.